2016
DOI: 10.1088/1741-2560/13/3/036016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the reference choice on scalp EEG connectivity estimation

Abstract: Overall, this study highlights that significant differences arise in scalp EEG functional connectivity and graph network properties, in dependence on the chosen reference. We hope that our study will convey the message that caution should be used when interpreting and comparing results obtained from different laboratories using different reference schemes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 102 publications
3
103
0
1
Order By: Relevance
“…In addition, REST is limited by the choice of head model employed. When an accurate, personalised, head model is available REST has been reported to be superior to other referencing methods in its ability to identify patterns of connectivity (Chella et al 2016). However, head models that are completely accurate in their representations of paths of electrical resistance in the brain are difficult to obtain, limiting the utility of this method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, REST is limited by the choice of head model employed. When an accurate, personalised, head model is available REST has been reported to be superior to other referencing methods in its ability to identify patterns of connectivity (Chella et al 2016). However, head models that are completely accurate in their representations of paths of electrical resistance in the brain are difficult to obtain, limiting the utility of this method.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the mean of the activity of all electrodes as a reference is commonly used and is widely accepted in ERP studies. However, other references, such as zero reference or REST [24,25] or other procedures such as Scalp Current Density [26], which is reference-free are alternatives for avoiding the influence of reference electrodes. The REST is in particular recommended for the spectral analysis, computation of coherence among difference electrode, and in functional connectivity studies.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this infinity reference (REST) is considered to be located far from all brain sources and scalp electrodes, and thus it induces a small effect on EEG signals. Previous studies have demonstrated that REST reference can approximately recover the EEG temporal waveform, power spectrum (Yao, 2001), EEG coherence (Marzetti et al, 2007), EEG connectivity patterns (Chella et al, 2016), and EEG network configuration (Qin et al, 2010). Also, simulation studies using a concentric three-sphere head model and a realistic head model (Zhai and Yao, 2004) have confirmed the accurateness of the REST reconstruction, even when a low-density montage was used (Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%